Clinical Safety Of Intra Dermal Rabies Vaccination (Idrv) With Purified Vero Cell Rabies Vaccine (Pvrv) - DR DURGA MADHAB SATAPATHY; DR TAPAS RANJAN BEHERA (International Journal of Pharma and Bio Sciences, 2011)
To study the clinical efficacy and side effects of Intra Dermal Rabies Vaccination (IDRV) using Purified Vero Cell Rabies Vaccine (PVRV) in the post exposure treatment of animal bites; a cross sectional, non-comparative, hospital based study was carried out among 123 patients attending the Anti Rabies Clinic (ARC) of a tertiary-care teaching hospital at Brahmapur in Orissa. All the 123 cases were treated with Inj. Verorab (manufactured by sanofi pasteur) by Thai Red cross (TRC) Regimen. Though all the patients complained of some type of local side effects, but these symptoms were relieved by simple administration of paracetamol and cetrizine orally for 3 days. The side effects (local symptoms) noted are local itch (47.9%), local pain (34.9%), fever (5.6%) and the local signs noted are local induration (87.8%), local erythema (15.4%). In 12.2% of the cases there were no signs and symptoms. All the patients were followed up to 1 year and found to be healthy & alive. Thus, this cost effective way of treating the animal bite cases using PVRV (Inj. Verorab) by TRC regime is recommended to reduce the burden of Rabies in India.